The Relevance of Zakāh Distribution at Indonesia’s National Zakāh Agency (BAZNAS) Pamekasan: The Perspective of ʿUmar ibn al-Khaṭṭāb - Fitriyah, Nurul; Haryanto, Rudy; Abidin, Zainal (El-Qist: Journal of Islamic Economics and Business (JIEB), 2023)
This study aims to explore the relevance of zakāh distribution practices at Indonesia’s National Zakāh Agency (BAZNAS) in Pamekasan through the lens of ʿUmar ibn al-Khaṭṭāb’s fiscal policies. Using a qualitative explanatory approach, the research investigates how contemporary zakāh distribution aligns with classical Islamic governance principles, particularly in achieving equity, justice, and socioeconomic empowerment. The findings reveal that while BAZNAS Pamekasan adheres to national zakāh regulations (Law No. 23 of 2011), its operational strategies—such as prioritization, the use of local databases, and both consumptive and productive schemes—demonstrate striking parallels with ʿUmar’s zakāh framework. Notably, ʿUmar’s policies on decentralized distribution, eligibility reclassification (e.g., exclusion of converts), and zakāh substitution (badal) during economic crises offer viable models for enhancing zakāh governance in Muslim-majority countries facing similar structural challenges. This study contributes to the global discourse on Islamic fiscal reform by proposing a historically grounded, yet adaptable model for zakāh distribution that integrates classical jurisprudence with modern regulatory frameworks. Future research may expand this framework to examine zakāh management across diverse geopolitical contexts, enabling comparative analysis of institutional efficiency, community impact, and policy innovation within the broader domain of Islamic public finance.